The Influence of the Simultaneous Addition of Fe2+ and Fe3+ on Changes in the Structural, Optical, and Electronic Properties of TiO2 Powder - Purnawan, Candra; Wahyuni, Endang Tri; Kartini, Indriana; Suherman, Suherman (Trends in Sciences, 2026)
Modification of TiO₂ powder to form TiO₂-Fe/Fe₂O₃ composites with simultaneous incorporation of Fe²⁺ and Fe³⁺ ions via a simple approach has been conducted. The characterization of photocatalyst composites has been carried out using FTIR, Raman, XRD, SAA, TEM, DRS, XPS, and VSM. The simultaneous incorporation of Fe²⁺ and Fe³⁺ ions has modified the structural, optical, and magnetic properties of TiO2 powder. Systematic variation of Fe²⁺: Fe³⁺ compositions (mole/mole) revealed that Fe³⁺ had a stronger impact than Fe²⁺. At low Fe³⁺ and Fe₂O₃ composition, interfacial interaction and heterojunction formation dominated, whereas higher levels promoted substitutional doping. At low Fe³⁺ composition (Fe2+: Fe3+ = 1:0.3 - 1:1), crystallite size increased (29.95 - 34.65 nm) but crystallinity decreased (62.34% - 57.99%), surface area increased (25.90 - 29.71 m2/g) but pore size decreased (0.097 - 0.085 cc/g), the bandgap narrowed (3.14 - 2.98 eV), and maghemite formation and magnetic moment decreased (36.83 - 17.66 emu/g). Whereas at Fe³⁺ higher ratio (Fe2+: Fe3+ = 1:1 - 1:3), the bandgap significantly narrowed (2.98 - 2.80 eV), crystallite size (34.65 - 27.30 nm) and crystallinity (57.99% - 49.27%) decreased, surface area (29.09 - 43.49 m2/g) and pore size (0.085 - 0.139 cc/g) increased, and hematite formation increased and magnetic moment decreased (17.66 - 14.86 emu/g). Furthermore, increasing the proportion of Fe₂O₃ in TiO₂ powder (TiO₂: Fe₂O₃) has enlarged the surface area and pore size, narrowed the bandgap, decreased the crystallite sizes and crystallinity, and improved magnetic properties. Photocatalytic evaluation under visible light showed that increasing Fe³⁺ and Fe₂O₃ enhanced both Methyl Violet (MV) degradation up to 84.54% and Cr(VI) reduction up to 36.55%, with stronger MV degradation indicating that Fe³⁺ mainly serves as an electron trap. HIGHLIGHTS Simultaneous addition of Fe2+ and Fe3+ ions in basic conditions to TiO2 powder has resulted in interesting changed properties, in which the Fe³⁺ effect is stronger than Fe²⁺. At low Fe³⁺ composition (Fe2+:Fe3+ = 1:0.3 - 1:1), the interfacial interaction and heterojunction formation dominated, bandgap narrowed, crystallite size increased but crystallinity decreased, surface area increased but pore size decreased, and maghemite formation and magnetic moment decreased. Whereas at Fe³⁺ higher ratio (Fe2+:Fe3+ = 1:1 - 1:3), the substitutional doping increased, bandgap significantly narrowed, crystallite size and crystallinity decreased, surface area and pore size increased, hematite formation increased and magnetic moment decreased. Increasing the proportion of Fe₂O₃ in TiO₂ powder (TiO₂:Fe₂O₃) has enlarged the surface area, narrowed the bandgap, decreased the crystallite sizes and crystallinity, and improved magnetic properties. Increasing Fe³⁺ and Fe₂O₃ enhanced both Methyl Violet (MV) degradation and Cr(VI) reduction under visible light. GRAPHICAL ABSTRACT